Punishment by Association: The Burden of Attending Court for Legal Bystanders. Issue 2 (9th May 2022) - Eife, Erin; Richie, Beth E.
Abstract : Scholars have shown how legal bystanders experience punishment at the hands of the state in their homes and neighborhoods, as well as jails and prisons. Other scholars have shown how bureaucratic processes, such as attending court, are punitive toward people charged with crimes. There is less information about how legal bystanders also experience punishment in courtrooms. In this article, we bridge the literatures between secondary prisonization and procedural punishment to illustrate how legal bystanders, such as family and friends of bond court defendants, experience punishment when attending bond court. We utilize courtroom ethnography of Central Bond Court in Chicago's Cook County and interviews with family and friends of people charged with a crime to illustrate this form of punishment in three themes: extraction, destabilization, and degradation. With these findings, we argue that secondary prisonization begins not at the point of incarceration, but at the moment a loved one's contact with the criminal legal system begins.